Metagenomic characterisation of bacterial communities associated with rice yellow stemborer, Scirpophaga incertulas - Freddy Kuok San, Yeo; Yin Hui, Cheok; Tommy Tsan Yuk, Lam; Yee Ling, Chong (Springer Nature, 2025)
Insects host diverse bacteria that play essential survival roles. The bacterial community composition is influenced by biotic and abiotic factors, including host plant genotypes. This study profiled the bacterial communities of yellow stemborer larvae using 16S rDNA amplicon sequencing. Larvae were fed three local rice landraces from Sarawak, and their bacterial diversity and abundance were compared. Altogether, nine samples were prepared, comprising three samples for each landrace: Bajong larvae (BJLV), Bario larvae (BRLV), and Bubok larvae (BBLV). A total of 21 phyla, 55 classes, 93 orders, 168 families, and 287 genera were detected. Proteobacteria dominated the microbiome, comprising 78.2% of the total community, with g_norank_f_Enterobacteriaceae (29.3%) as the most abundant genus. Diversity tests indicated bacterial community homogeneity among larvae feeding on different landraces, suggesting vertical bacterial transmission from adult female yellow stemborers to their offspring.